Analisis Sosiologis Cerpen “Si Padang” Karya Harris Effendi Thahar - Yasnur Asri (Humaniora, 2011)
This paper aims at describing the reflection of social reality of Minangkabau Society in the short story entitled “Si Padang” written by Harris Effendi Thahar. The theory used in this study is the sociology of literature by using the mimetic approach. The analysis begins from the text by explaining the social factors in the text, then examining the social factors in the society that become the topic of the story. The result of the analysis shows that the short story “Si Padang”is the short story that is able to describe the social reality of Minangkabau society at present that is the inharmonious relation between maternal uncle and his nephew. As the reflection of the Minangkabau social reality this short story is social justification of Hoggart’s opinion that states the literary work at all level is enlightened by the prescript values and applied values. Because of that what Harris has written shows that his work is truly integrated with the individual and society life in the structure of the society.